Clinicopathologic comparison of basal cell carcinoma among a diverse patient population in Los Angeles County - Esther Choi; Martha A. Oberg; Maya Hijazi; Luke Hall; Kimberly A. Miller; Arjun Mehta; Stephen Capone; Gino K. In (Wiley, 2024)
Abstract Introduction Basal cell carcinoma (BCC) is the most common malignancy in the United States. The majority of cases are identified in Non‐Hispanic Whites (NHW) and are far less demonstrated in patients of colour (POC). However, the Hispanic population represents a large and growing proportion of the US population, and skin cancer diagnoses in Hispanics are rising. Thus, the goal of this study is to examine clinicopathologic differences between BCC in Hispanics versus NHW. Methods A retrospective chart review of Hispanic and NHW patients with BCC at Los Angeles County + USC Medical Center from January 2018 to March 2020 was performed. In total, 101 BCC samples from the first 100 patients identified of Hispanic ancestry, as well as 50 BCC samples identified from the first 50 patients identifying as NHW, were included for analysis. Patient characteristics (age, sex, medical history, and ethnicity), as well as tumour characteristics (location, subtype, tumour depth, and perineural invasion), were collected. We used between subjects t‐tests for continuous variables, and chi‐square tests for categorical variables. Results In total, 151 specimens were collected amongst 122 subjects (79 Hispanics and 43 NHW patients). Among NHW, the majority of patients (74.4%) were men, but among the Hispanic population, the majority (68.4%) were female (p < 0.001). Prior history of other skin cancer was more common among NHW (67.4%) than Hispanics (31.6%) (p=<0.001). The Hispanic population had a significantly higher proportion of head and neck tumours (p = 0.0004) but a lower proportion of extremity tumours (p = 0.001) compared to NHW. Pigmented BCC was significantly more common among Hispanic patients (p < 0.01). Finally, within the Hispanic group, there was a significant association between sex and histology (p = 0.004), with Hispanic men demonstrating more aggressive mix histology compared to Hispanic women. Discussion Our study supports the notion that BCC disparities occur among POC compared to NHW. This includes variations in epidemiologic factors such as sex and past medical history, primary tumour location, and pathologic characteristics. Further research should be conducted to identify additional differences in skin cancer presentation in POC to reduce the gaps in skin cancer knowledge and care.